Natural History Analysis of 101 Severe Dysplasia and Esophageal Carcinoma Cases by Endoscopy. (30th March 2017) - Wang, Jin-Wu; Guan, Chen-Tao; Wang, Li-Li; Chang, Ling-Yun; Hao, Chang-Qing; Li, Bian-Yun; Lu, Ning; Wei, Wen-Qiang
Abstract : Objectives . Our research is to realize the natural history from dysplasia to carcinoma and to provide evidence for exploring proper screening intervals. Methods . After the onset endoscopy screening, 2093 of the patients participated in the endoscopic follow-up voluntarily. Totally, 101 severe dysplasia and carcinoma cases, either diagnosed in the first endoscopy without treatment or diagnosed in the second endoscopy, were included in our study. We compared the pathologic results of their two endoscopies and calculate the mean and median progression time. Results . Of the 39 severe dysplasia cases diagnosed by the onset endoscopy, only 8 progressed to carcinoma. For severe dysplasia cases diagnosed by the follow-up endoscopy, mean progression times are 55.0, 49.8, and 38.0 months and median progression times are 43, 56, and 31 months for esophagitis, mild dysplasia, and moderate dysplasia, respectively. For superficial carcinoma cases diagnosed by the second endoscopy, mean progression times are 76.0, 57.4, and 47.0 months and median progression times are 77, 63, and 35 months for mild dysplasia, moderate dysplasia, and severe dysplasia, respectively. Conclusions . Population-based severe dysplasia cases may have much lower carcinoma progression rate than specific-selected ones. The progression time for most enrolled cases seems longer than that of the recent screening protocol recommended.